2022
DOI: 10.3389/fped.2022.951039
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perceptions of mothers towards childhood vaccination in Greece: lessons to improve the childhood COVID-19 vaccination acceptance

Abstract: BackgroundMaternal attitudes and beliefs have been shown to influence childhood vaccination coverage, resulting in under-vaccination, non-vaccination, and vaccination delay. This study aimed to investigate the mothers' attitudes and perceptions about vaccination for their children in Greece.MethodsThis was an online cross-sectional study, conducted from 4 April to 8 June 2020. A self-administered questionnaire was used to collect information about mothers' and their children's socio-demographic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 87 publications
1
5
1
Order By: Relevance
“…In our study, 1,943 (91.4%) of the mothers/caregivers indicated that they had trust in childhood vaccination, which was higher than the 48.2—66% reported in other studies conducted in the Washington State and Saudi Arabia [ 78 , 79 ], slightly higher than the 84% vaccine acceptance due to trust in six Southeast Asian countries [ 77 ] and lower than 91.6% reported amongst mothers in Greece [ 74 ]. Trust in childhood vaccination depended on the socio-demographic characteristics; sex, relationship with child(ren), educational status, occupation of parents/monthly income, as well as on the sources of vaccine information.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In our study, 1,943 (91.4%) of the mothers/caregivers indicated that they had trust in childhood vaccination, which was higher than the 48.2—66% reported in other studies conducted in the Washington State and Saudi Arabia [ 78 , 79 ], slightly higher than the 84% vaccine acceptance due to trust in six Southeast Asian countries [ 77 ] and lower than 91.6% reported amongst mothers in Greece [ 74 ]. Trust in childhood vaccination depended on the socio-demographic characteristics; sex, relationship with child(ren), educational status, occupation of parents/monthly income, as well as on the sources of vaccine information.…”
Section: Discussioncontrasting
confidence: 80%
“…The 95.5% proportion of respondents with good knowledge of childhood vaccination in this study was high compared with the 86% reported among Saudi Arabian mothers [ 65 ], and very high compared with the 27 – 37.2% reported by other authors among Indonesian, Egyptian and Ethiopian parents [ 53 , 70 72 ], and similar to the 91.7 – 94.4% reported among mothers in Italy and Greece [ 73 , 74 ]. In another study on mothers' knowledge towards children's vaccination in Lebanon, good knowledge depended on physician’s communication [ 1 ].…”
Section: Discussionsupporting
confidence: 79%
“… 49 The same study also showed that the majority of participants are against the immediate vaccination of children after the release of new vaccines. 49 In addition, many COVID‐19 vaccines were not approved for young children, so parents may think vaccines were unsafe for their children and themselves.…”
Section: Discussionmentioning
confidence: 88%
“…A possible explanation could be the parental fear of any long‐term health problem caused by the vaccine that will interfere with their ability to raise their children. Supporting this hypothesis, a recent study showed that only a small percentage of mothers in Greece did not have doubts about the efficacy and safety of new vaccines 49 . The same study also showed that the majority of participants are against the immediate vaccination of children after the release of new vaccines 49 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation